(untitled) (Journal of Parents and Teachers, 2025)
Schools today welcome pupils from many different backgrounds, and teachers need to help every learner feel included. The European project EUPeace supports this by giving future teachers international experiences and practical tools to work with diversity. Through its School for All concept, it promotes values of peace, justice, and equity, while encouraging collaboration and creativity. The aim is to prepare teachers to feel confident, adaptable, and ready to build inclusive classrooms.